Relasi Kuasa, Agama, dan Budaya Lokal dalam Dinamika Kehidupan Masyarakat Plural - Ahmad Syamsuddin Mappangara; Siti Hajar Nurannisa Kamaruddin; Muhammad Arfan Tadulako Basri (Nalar Bhinneka: Jurnal Humaniora, 2026)
Power relations between religion and local culture are an ongoing dynamic that continually shifts within the plural society of Indonesia. This study aims to analyze the patterns of power relations occurring between religious authorities and local cultural traditions in plural communities. The research was conducted in three locations in South Sulawesi Province. The method used is multisite ethnography with data collection through participatory observation, in-depth interviews, and document analysis during the period 2023–2025. The findings reveal four patterns of relations: symbiotic accommodation, cultural resistance, religious dominance, and cultural hybridization. Overall, local culture demonstrates significant resilience in maintaining its existence despite normative pressures from formal religious authorities. This study concludes that the negotiation between religion and local culture is dynamic, contextual, and non-linear, requiring policy approaches that are sensitive to local diversity.